1969
DOI: 10.1111/j.1432-1033.1969.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Protein Synthesis in the Nucleus and Cytoplasm of HeLa Cells in the Presence of Actinomycin, Puromycin and Hydroxyurea

Abstract: A comparison has been made between the synthesis of histones, other nuclear proteins and cytoplasmic proteins after treatment of HeLa cells with substances known to alter their metabolic state : actinomycin, puromycin and hydroxyurea. The use of sensitive methods involving amino acid analysis and measurement of specific radioactivity has revealed differential responses to the action of the different inhibitors. Analysis of these findings as a function of the effects of these inhibitors on other metabolic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1970
1970
1978
1978

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Our results agree with those in the literature which suggest that histone synthesis does continue at a reduced level in the absence of concurrent DNA synthesis (15,16,29,35,43). This is in disagreement with Bloch and coworkers, and Flamm and Birnstiel who found histone synthesis continuing at the normal rate in the presence of DNA synthetic blocking agents (6,14).…”
Section: Discussionsupporting
confidence: 70%
“…Our results agree with those in the literature which suggest that histone synthesis does continue at a reduced level in the absence of concurrent DNA synthesis (15,16,29,35,43). This is in disagreement with Bloch and coworkers, and Flamm and Birnstiel who found histone synthesis continuing at the normal rate in the presence of DNA synthetic blocking agents (6,14).…”
Section: Discussionsupporting
confidence: 70%
“…Studies using diverse systems have implied an intimate relationship between histone biosynthesis and DNA replication (Elgin andWeintraub 1975, Johnson, Douvas andBonner 1974) . A number of investigations have indicated, however, that the interlinking between DNA and histone synthesis may not always be obligatory (Gurley and Hardin 1968, Sadgopal and Bonner 1969, Yarbro 1967, Zampetti-Bosseler, Malpoix and Fievez 1969, Ontko and Moorehead 1964 . Although non-histone proteins of chromatin are intimately associated with DNA, it has been found that there is no strict correspondence between synthesis of DNA and turnover of non-histone proteins (Holbrook, Evans and Irvin 1962, Rovera and Baserga 1971, Stein and Baserga 1970 .…”
Section: Introductionmentioning
confidence: 99%